Rancang Bangun dan Uji Performa Sistem Kendali Pemberian Fluida Permesinan MQL Berbasis Arduino - Dinata, Gerry Gardika Surya; Muttaqin, Aris Zainul; Darsin, Mahros (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
In machiningÂ excessive use of cutting fluid can have a negative impact to theÂ enviroment. An alternative to overcome this problem is by using the minimum quantity lubrication method (MQL). In MQL method the cutting fluid is flowed by compressedÂ air. This research aim to design and implement an Arduino-based controller for further minimize the use of cutting fluid in MQL system. It was programmed that the pump would only work when the tool temperature beyond 70 oC and vice versa. Observation shows that the controller work accordingly. Other experiments were carried out to check the fluid consumption with Taguchi method. It was proof that applying the controller was able to reduce the fluid consumption.